2022
DOI: 10.1002/dta.3389
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 18‐methyl steroids: Case report on a forensic urine sample and corresponding dietary supplements

Abstract: The detection of a putative 18‐methyl‐19‐nortestosterone metabolite in a forensic bodybuilder's urine sample collected as part of a criminal proceeding has triggered a follow‐up investigation. Four different dietary supplements in the possession of the suspect were examined with regard to possible precursor steroids. This led to the detection of the declared ingredient methoxydienone, which was confirmed by both, GC–MSMS and LC‐HRMSMS. As neither 18‐methyl‐testosterone, nor 18‐methyl‐19‐nortestosterone were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The fact that, eventually, confirmation of in vitro metabolism study data with authentic elimination study specimens is vital for routine doping controls was demonstrated in a case report by Thieme et al 31 In the context of a forensic investigation, the biotransformation of the AAS methoxydienone (Figure 1, 2 ) was studied employing the aforementioned HepG2‐based in vitro metabolism approach as well as urine samples collected after oral administration to a human volunteer, and the urinary metabolite observed by means of routine doping control analytical procedures, presumably 18‐methylnorandrosterone, was not generated in vitro but abundantly observed in post‐administration urine specimens.…”
Section: Anabolic Agentsmentioning
confidence: 97%
“…The fact that, eventually, confirmation of in vitro metabolism study data with authentic elimination study specimens is vital for routine doping controls was demonstrated in a case report by Thieme et al 31 In the context of a forensic investigation, the biotransformation of the AAS methoxydienone (Figure 1, 2 ) was studied employing the aforementioned HepG2‐based in vitro metabolism approach as well as urine samples collected after oral administration to a human volunteer, and the urinary metabolite observed by means of routine doping control analytical procedures, presumably 18‐methylnorandrosterone, was not generated in vitro but abundantly observed in post‐administration urine specimens.…”
Section: Anabolic Agentsmentioning
confidence: 97%
“…Improvements regarding test methods and enhanced knowledge concerning metabolic and degradation processes concerning the class of anabolic‐androgenic steroids (AAS) were presented by various examples, for example, by the first report on findings attributed to “methoxydienone” (13β‐ethyl‐3‐methoxygona‐2,5(10)‐dien‐17‐one) and its biotransformation product in human urine 6 . The fact that, besides relevant human metabolic reactions, also microbial degradation of urinary steroids necessitates monitoring and consideration was addressed by the suggestion of employing a degradation marker compatible with routine AAS screening protocols.…”
mentioning
confidence: 99%